A Proposal of Speed Zone Classification in Basketball: A New-Criteria Based on Maximum Registered Values - Rojas-Valverde, Daniel (2022)
The quantification of training load has become mandatory for coaches and team staff. Within the analyzed variables, distance covered at different speed zones is one of the most studied. However, there is no consensus in the definition of speed zones in the published articles about each team sport, so it makes difficult a comparison between them. Therefore, the purposes of this article were to establish a criteria standard in the classification of speed zones in team sports and to analyze its practical application in basketball. Five speed categories were established for basketball following the methodology described above: 0-10km/h, >10-13.8 km/h, >13.8-17.6 km/h, >17.6-21.5 km/h, and >21.5 km/h. The results showed differences between periods in high-speed displacements and sprints, maximum speed, total decelerations, and accelerations. In conclusion, the categorization of workload based on standard deviation according to maximum speed could be a viable option to individualize the analysis of distance covered per speeds in team sports such as basketball. Its use may lead to a better understanding and contextualization of the locomotion data in specific sports and teams.